1959
DOI: 10.1172/jci103784
|View full text |Cite
|
Sign up to set email alerts
|

Platelets as a Source of Serum Acid Nitrophenylphosphatase*

Abstract: Recent interest in serum enzyme activity in pathological conditions has led to renewed curiosity concerning the source of the enzymes present in serum under normal conditions. Since blood platelets contain acid phosphatase (1-8), it seemed possible that they might liberate this enzyme during blood coagulation. This possibility was investigated by comparing the acid phosphatase activity of serum prepared from platelet-rich and platelet-poor plasmas. Preliminary studies suggested that the platelets contribute vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1961
1961
1979
1979

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…been measured by exposing the platelets to glass under standardized conditions (Wright 1941, Moolten & Vroman 1949, Marx & Derlath 1957, Hellem 1960, and platelet aggregation has been studied by observing plasma under various conditions (Bergsagel 1956, Sharp 1958, and Waaler 1959. In uiuo, similar phenomena have been studied by Bizzozero (1 882), Eberth & Schimmelbusch (1886) and more recently by Zucker (1947) and Hugues ( 1953).…”
supporting
confidence: 55%
“…been measured by exposing the platelets to glass under standardized conditions (Wright 1941, Moolten & Vroman 1949, Marx & Derlath 1957, Hellem 1960, and platelet aggregation has been studied by observing plasma under various conditions (Bergsagel 1956, Sharp 1958, and Waaler 1959. In uiuo, similar phenomena have been studied by Bizzozero (1 882), Eberth & Schimmelbusch (1886) and more recently by Zucker (1947) and Hugues ( 1953).…”
supporting
confidence: 55%
“…Apart from some of the early descriptions of the platelet (36)(37)(38) and some more modern studies in vivo (39,40), by far the bulk of knowledge concerning the properties of the platelets has come from in vitro studies. These have revealed that under various stimuli resulting in aggregation, platelets may release some or all of their pharmacological contents which include histamine (41), serotonin (42,43), ATP (44), ADP (45), fibrinogen (46), adrenaline (47), noradrenaline (48), lysosomes (49), acid phosphatase (49), elastase (50), and a sofar unidentified heat-stable factor, of tool wt less than 10,000, which causes increased vascular permeability (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…More promising are the hypotheses which postulate the significance of arylsulfatase during the metabolism of mucopolysacharides (22). There is also the possibility in the same manner as in the case of acid phosphatase (23) and /?-glucuronidase (24) to observe serum-plasma difference in connection with release reaction of platelets.…”
Section: Tabu Imentioning
confidence: 97%